2021
DOI: 10.1039/d1ra02733f
|View full text |Cite
|
Sign up to set email alerts
|

High performance polypyrrole/SWCNTs composite film as a promising organic thermoelectric material

Abstract: PPy/SWCNTs composite films with high thermoelectric performance were prepared by chemical interfacial polymerization under a controlled low temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…This interaction will enhance the electrical conductivity by acquiring more carriers, as PPy is rich with charge carriers (see Figure 3 d), but at certain layer thickness of highly pure PPy (with no defects/agglomerations or residuals). It is worth mentioning that the recorded PF value of the optimum nanocomposite sample in this study, PW2, is greater than the PF values of MWCNT/PPy and SWCNTs/PPy composites reported in the literature [ 36 , 37 ].…”
Section: Resultscontrasting
confidence: 69%
“…This interaction will enhance the electrical conductivity by acquiring more carriers, as PPy is rich with charge carriers (see Figure 3 d), but at certain layer thickness of highly pure PPy (with no defects/agglomerations or residuals). It is worth mentioning that the recorded PF value of the optimum nanocomposite sample in this study, PW2, is greater than the PF values of MWCNT/PPy and SWCNTs/PPy composites reported in the literature [ 36 , 37 ].…”
Section: Resultscontrasting
confidence: 69%
“…As shown in Figure d,e, the TE performance is in the upper middle level among all kinds of polymer semiconductors and carbon material composites reported in the literature as Figure e,f lists. ,,, It is worth mentioning that the σ value of the D4 film (4717.8 ± 41.51 S cm –1 ) is the highest among the composites based on commercial carbon fillers and organic semiconductors.…”
Section: Resultsmentioning
confidence: 79%
“…17 Liang et al have reported synthesis techniques of different nanostructures of PPy and their TE performances. 15 Numerous research works have been reported supporting the compatibility of PPy and PPy/carbonbased material composites as OTE, 18 such as PPy/Graphene nanosheets composites, 19 PPy/reduced graphene oxide composites, 20 PPy/SWCNT composites, 21 PPy/MWCNT composites, 22 PPy/helical carbon nanotube composites, 23 etc.…”
Section: Poly(34e T H Y L E N E D I O X Y T H I O P H E N E ) : P O L...mentioning
confidence: 99%